A Social Psychology Perspective on Physical Education for Second-Year Students at Hanoi Capital University, Vietnam - Nhu Quynh, Luu Thi (Environment and Social Psychology, 2026)
This study analyzes the current status of Physical Education for second-year students at Hanoi Capital University through a social psychology lens. Four key areas were evaluated: (i) Physical Education program content, (ii) physical training facilities, (iii) use of exercises for general physical fitness development, and (iv) current physical fitness levels. The research employed a mixed-methods approach with 40 second-year male Physical Education majors. Results indicate that while the program meets basic requirements, it lacks components addressing psychological needs like autonomy, competence, and relatedness from Self-Determination Theory (SDT). Facilities are insufficient, and exercise usage fails to account for motivational differences and group dynamics. Physical fitness levels are average but limited in endurance and speed, correlating with low self-efficacy and social support. The study proposes integrating Social Identity Theory, Theory of Planned Behavior (TPB), and Social Cognitive Theory to enhance student engagement, motivation, and long-term physical activity habits.